A Multilayer Surface Temperature, Surface Albedo, and Water Vapor Product of Greenland from MODIS - Dorothy K. Hall; Richard I. Cullather; Nicolo E. DiGirolamo; Josefino C. Comiso; Brooke C. Medley; Sophie M. Nowicki (Remote Sensing, 2018)
A multilayer, daily ice surface temperature (IST)–albedo–water vapor product of Greenland, extending from March 2000 through December 2016, has been developed using standard MODerate-resolution Imaging Spectroradiometer (MODIS) data products from the Terra satellite. To meet the needs of the ice sheet modeling community, this new Earth Science Data Record (ESDR) is provided in a polar stereographic projection in NetCDF format, and includes the existing standard MODIS Collection 6.1 IST and derived melt maps, and Collection 6 snow albedo and water vapor maps, along with ancillary data, and is provided at a spatial resolution of ~0.78 km. This ESDR enables relationships between IST, surface melt, albedo, and water vapor to be evaluated easily. We show examples of the components of the ESDR and describe some uses of the ESDR such as for comparison with skin temperature, albedo, and water vapor output from Modern Era Retrospective analysis for Research and Applications, Version 2 (MERRA-2). Additionally, we show validation of the MODIS IST using in situ and aircraft data, and validation of MERRA-2 skin temperature maps using MODIS IST and in situ data. The ESDR has been assigned a DOI and will be available through the National Snow and Ice Data Center by the summer of 2018.